2016
DOI: 10.1111/exd.12913
|View full text |Cite
|
Sign up to set email alerts
|

Collagens XV and XVIII show different expression and localisation in cutaneous squamous cell carcinoma: type XV appears in tumor stroma, while XVIII becomes upregulated in tumor cells and lost from microvessels

Abstract: As the second most common skin malignancy, cutaneous squamous cell carcinoma (cSCC) is an increasing health concern, while its pathogenesis at molecular level remains largely unknown. We studied the expression and localisation of two homologous basement membrane (BM) collagens, types XV and XVIII, at different stages of cSCC. These collagens are involved in angiogenesis and tumorigenesis, but their role in cancer development is incompletely understood. Quantitative RT-PCR analysis revealed upregulation of coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 38 publications
1
28
1
Order By: Relevance
“…In this respect, it is important to note, that the structure of basement membrane is altered in AK and cSCCIS, indicating that alterations in the microenvironment of the premalignant and noninvasive lesions is important in their progression to invasive cSCC. 76 In conclusion, the authors have identified a lncRNA, PRECSIT, that is specifically expressed by cSCC cells in culture and in vivo, and show that it is regulated by p53 ( Figure 5). The levels of activated transcription factor STAT3 are up-regulated by PRECSIT, and this in turn upregulates the expression of several invasion-associated MMPs, that is, MMP-1 and MMP-13, which cleave fibrillar collagens, and MMP-3 and MMP-10, which can cleave a multitude of other extracellular matrix and basement membrane components, including type IV collagen, fibronectin, and laminin, and can activate latent MMP-1 and MMP-13.…”
Section: Lncrna Precsit In Csccmentioning
confidence: 86%
“…In this respect, it is important to note, that the structure of basement membrane is altered in AK and cSCCIS, indicating that alterations in the microenvironment of the premalignant and noninvasive lesions is important in their progression to invasive cSCC. 76 In conclusion, the authors have identified a lncRNA, PRECSIT, that is specifically expressed by cSCC cells in culture and in vivo, and show that it is regulated by p53 ( Figure 5). The levels of activated transcription factor STAT3 are up-regulated by PRECSIT, and this in turn upregulates the expression of several invasion-associated MMPs, that is, MMP-1 and MMP-13, which cleave fibrillar collagens, and MMP-3 and MMP-10, which can cleave a multitude of other extracellular matrix and basement membrane components, including type IV collagen, fibronectin, and laminin, and can activate latent MMP-1 and MMP-13.…”
Section: Lncrna Precsit In Csccmentioning
confidence: 86%
“…Progression of cSCCs is characterized by an alteration of basement membrane structure at an early stage, and by an eventual loss of basement membrane at invasive stage ( Karppinen et al, 2016 ). There is also evidence that the cellular expression of lncRNAs is dependent on the composition and structure of the extracellular matrix ( Zhuang et al, 2013 ; Li et al, 2017 ), indicating that the lncRNA expression varies depending on the activation of different adhesion receptors.…”
Section: Resultsmentioning
confidence: 99%
“…There is increasing evidence that the role of tumor microenvironment presents a significant role in initiation and progression of cSCC. The composition of epidermal basement membrane and dermal extracellular matrix, influx of inflammatory cells and presence of microbial structures have been revealed to affect cSCC progression …”
Section: Introductionmentioning
confidence: 99%